PENGARUH PROMOSI PRODUK HUAWEI TERHADAP MINAT BELI KONSUMEN DI INDONESIA - Azzahra, salsa (Journal for Management Student (JFMS), 2023)
The study conducted in Bandar Lampung, Indonesia, delved into the impact of product advertising on consumer purchase intentions. Employing exploratory research methods, the investigation assessed feasibility, significance, and considerations. With a population of 95 randomly selected respondents, the construct reliability value exceeded 0.7, deemed acceptable for exploratory research. Utilizing hypothesis testing, the research aimed to validate claims about the population based on sample data, specifically probing the influence of consumer perceptions of product advertising on purchasing intentions in Indonesia. Furthermore, the study explored the interplay between gender, occupation, age, and consumers' interest in purchasing Huawei products.   Keywords : product promotion, purchase interest, marketing.